Zinc Tin Oxide (ZTO) electron transporting buffer layer in inverted organic solar cell - Oo, Than Zaw (2013)
Solution processed, high electron mobility and highly transparent Zinc Tin Oxide (ZTO) was successfully exploited as electron transporting buffer layer in an inverted organic solar cell. The device configuration of FTO/ZTO/P3HT:PCBM/WO3/Ag was employed. For comparison, an identical device using a sol–gel derived TiOx electron extracting layer was also fabricated. Increased short-circuit density (Jsc) and open-circuit voltage (Voc) were generated in the devices with ZTO layer in comparison to the ones with TiOx layer. It is attributed to a better electron transporting, hole blocking capacities and reduced recombination probabilities at electron collecting electrode with ZTO layer. A power conversion efficiency of 3.05% was achieved with ZTO devices.